The Implementation of Group Investigation Technique in Teaching Writing Hortatory Exposition Text for Eleventh Grade Students of Senior High School (RETAIN, 2019)
Abstrak Saat ini menulis menulis menjadi salah satu keterampilan yang paling sulit untuk dikuasai. Hal ini menjadi tantangan bagi guru untuk mengatasi masalah ini dalam rangka membantu siswa mencapai tujuan dari pembelajaran. Namun, banyak guru mulai memperluas cara mereka dalam mengajar dengan menerapkan metode atau teknik yang berbeda untuk mencapai tujuan pengajaran. Salah satunya yaitu penerapan teknik investigasi kelompok dalam pengajaran menulis teks eksposisi hortatori. Penelitian ini bertujuan untuk mendeskripsikan implementasi investigasi kelompok, konten dari tulisan siswa, dan respon siswa setelah diajarkan menggunakan teknik investigasi kelompok. Penelitian ini termasuk dalam penelitian kualitatif dengan subjek penelitian seorang guru dan 30 siswa kelas XI SMA. Dalam hal ini, data dikumpulkan melalui observasi, kuesioner terbuka, dan hasil tulisan siswa. Hasil penelitian ini menunjukkan bahwa guru sudah menerapkan tahapan teknik investigasi kelompok secara berurutan meskipun ada beberapa bagian dari kegiatan yang dimodifikasi. Selain itu, hasil tulisan siswa menunjukkan bahwa siswa dapat mengembangkan konten dengan baik dalam menulis teks eksposisi hortatori. Kemudian, siswa juga memberikan respon positif terhadap teknik yang telah diterapkan oleh guru. Kata Kunci: Investigasi Kelompok, Menulis, Mengajar Menulis, Teks Eksposisi Hortatory Abstract Nowadays, writing becomes one of the most difficult skills to master. It becomes a challenge for teachers to overcome this problem in order to help students to achieve the goal of learning. However, many teachers started to expand their way of teaching by implementing different method or technique in order to achieve the goal of teaching. One of them is a group investigation technique in teaching writing hortatory exposition text. Therefore, the research is aimed to describe the implementation of group investigation, the students’ content in writing and the students’ response after being taught using group investigation technique. In this case, this research belongs to a qualitative study. The subject of this study was a teacher and 30 eleventh grade students of senior high school. The data was collected through observation, open-ended questionnaire, and students’ writing results. The result of this study showed that the teacher already implemented the stages of group investigation technique sequentially even though there were some parts of the activity which is modified. In addition, the result of the students’ writing also showed that the students were able to develop good content in writing hortatory exposition text. The students also gave a positive response to the technique that had been applied by the teacher. Keywords: Group investigation, Writing, Teaching Writing, Hortatory Exposition text.